2023
DOI: 10.1002/smll.202300915
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Fabrication of Micro/Nanostructured Polyethylene/Carbon Nanotubes Foam with Robust Superhydrophobicity, Excellent Photothermality, and Sufficient Adaptability for All‐Weather Freshwater Harvesting

Abstract: The integration of fog collection and solar‐driven evaporation has great significance in addressing the challenge of the global freshwater crisis. Herein, a micro/nanostructured polyethylene/carbon nanotubes foam with interconnected open‐cell structure (MN‐PCG) is fabricated using an industrialized micro extrusion compression molding technology. The 3D surface micro/nanostructure provides sufficient nucleation points for tiny water droplets to harvest moisture from humid air and a fog harvesting efficiency of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…In particular, functional coatings inevitably work in complex environments, such as small-particle erosion or rainfall impact, in practical applications. 54–56 Therefore, a series of tests (resistance to sandstone impact, water-current impact, corrosion by acid, alkali and salt solution, sandpaper abrasion, and high/low temperature variations) were undertaken (Fig. 3g–i and Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, functional coatings inevitably work in complex environments, such as small-particle erosion or rainfall impact, in practical applications. 54–56 Therefore, a series of tests (resistance to sandstone impact, water-current impact, corrosion by acid, alkali and salt solution, sandpaper abrasion, and high/low temperature variations) were undertaken (Fig. 3g–i and Fig.…”
Section: Resultsmentioning
confidence: 99%
“…146 Therefore, the direct design of 3D HS is important for practical applications. 147,148 However, in addition to being driven by Laplace pressure differences, wettability gradients, and capillary forces, the principle of designing 3D HS for fog collection is often driven by gravity. 149 Gravity-driven HS are often designed with an open surface, which increases the risk of the evaporation of the collected fog.…”
Section: The Development Of Fog Collection With Hierarchically Struct...mentioning
confidence: 99%
“…Huang et al demonstrated that the design of vertically aligned channels in an aerogel evaporator can reduce heat loss and promote water transport at gas–liquid interfaces, thus achieving enhanced evaporation efficiency . Additionally, appropriate surface design has also been shown to improve water evaporation performance. , Zhu et al designed a water lily inspired evaporator with a hydrophobic surface, avoiding the accumulation of salt crystals on the surface and achieving a better brine desalination performance than a conventional hydrophilic evaporator . Yu et al constructed a PVA hydrogel with a sharply dimpled surface to increase heat flux, promote water diffusion, and thus achieve a high solar steam generation performance .…”
Section: Introductionmentioning
confidence: 99%